Game changer—talent transfer pathways in sport: a systematic review - Green, Adeline; Fleischman, David; Mulcahy, Rory; Kean, Bridie (Frontiers in Sports and Active Living, 2024)
Research Question: Talent transfer, an accelerated sport pathway to expertise, holds considerable appeal for sports organisations. As an emerging area of academic research across a range of sport disciplines, there is opportunity for to advance knowledge and practice. This review aimed to a) explore how talent transfer has been defined, to develop a synthesised definition; b) systematically identify the factors that influence talent transfer; and c) investigate how theory underpins and enhances understanding of talent transfer.Research Methods: A systematic review was conducted of 12 peer-reviewed journal articles on talent transfer using the PRISMA approach.Results and Findings: Aiming for a comprehensive, multidisciplinary perspective, the results: introduce a clear, synthesised conceptualisation of talent transfer as an accelerated sport pathway in which a highly trained athlete in one sport (donor sport), transitions to a new sport (recipient sport) with the potential of achieving highperformance success; systematically map influencing factors; and outline considered theories. Factors influencing talent transfer span individual, task-related, and environmental constraints. The review exposes a scarcity of theoretical foundation in current research, suggesting ecological dynamics as a promising approach to advance research and practice.Implications: Practical and theoretical implications arise, emphasising the usefulness of a synthesised definition and a multifactorial approach for designing, implementing, evaluating, and researching talent transfer pathways. This benefits sports administrators, managers, and researchers.